Private health insurance, mental health and service use in Australia - Butterworth, P; Whiteford, H; Leach, L.S; Leach, L (My University, 2012)
Objective: To report on the private health insurance (PHI) status of individuals with and without a mental health problem, and examine whether PHI status is associated with access to psychological services. Methods: This is a descriptive study of nationally representative population-based data collected in 2009 (HILDA) with participants aged 15–93 (n = 13,301). Key measures included: PHI status (categorised as ‘hospital cover only’, ‘extras cover only’, or ‘both hospital and extras cover’); mental health status (categorised as ‘have a mental health problem’ or ‘do not have a mental health problem’ using the Mental Health Index (MHI) of the Medical Outcomes Study Short Form); mental health service use (access to a mental health professional (psychologist/psychiatrist) in the past 12 months categorised as ‘yes’ or ‘no’). Results: Individuals with a mental health problem were less likely to have PHI than those without a mental health problem. However, PHI was not associated with access to a mental health professional in the past 12 months. Conclusions: The findings suggest that while the discrepancy in PHI status is a marker of inequity between those with and without a mental health problem, it is not a key factor in facilitating access to mental health services.
Australian & New Zealand Journal of Psychiatry
Keywords: Health -- Health Insurance; Health -- Mental; Health and wellbeing; Health; Health Insurance; Mental; Health and wellbeing